Short and long term effects of granulocyte colony-stimulating factor during induction therapy in acute myeloid leukemia patients younger than 65: Results of a randomized multicenter phase III trial - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
This prospective multicenter phase III clinical trial was designed to assess efficacy and safety of G-CSF as an adjunct to de novo AML remission induction therapy (www.clinicaltrials.gov.NCT00820976). Patients' characteristics were similar in both arms. G-CSF improved severity and duration of leukopenia. Three-year OS were similar (25.6 +/- 5.1% vs. 31.8 +/- 5.6%) in both arms except for patients with myeloblastic features. Significant factors for better survival were the use of G-CSF (p = 0.049), female sex (p = 0.05) and single induction cycle (p < 0.001) in multivariate analysis. Female patients performed better than male patients. Better survival obtained among female AML patients needs to be validated within the context of cytogenetic analysis. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Granulocyte colony-stimulating factor; Acute myeloid leukemia; Induction; Survival; ACUTE MYELOGENOUS LEUKEMIA; PLACEBO-CONTROLLED TRIAL; SOUTHWEST-ONCOLOGY-GROUP; ELDERLY-PATIENTS; DOUBLE-BLIND; ADULT PATIENTS; GROWTH-FACTORS; G-CSF; FEBRILE NEUTROPENIA; PROGNOSTIC-FACTORS